Non-atherosclerotic coronary artery aneurysms: two case reports - Chia, H. (1997)
Non-atherosclerotic isolated coronary artery aneurysm is not common. Two cases of non-atherosclerotic isolated coronary artery aneurysm, with similar presentations but different management strategies were presented. The patients were well four and six years later, respectively. The definition, incidence, causes, presentation, complications, investigations, management, and prognosis of coronary artery aneurysms are discussed. The difficulties of determining pathogenesis and different management strategies are highlighted. An isolated coronary artery aneurysm should be managed on its merits.   Keywords: coronary artery aneurysms